2008
DOI: 10.1002/bit.21849
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SHF and SSF processes from steam‐exploded wheat straw for ethanol production by xylose‐fermenting and robust glucose‐fermenting Saccharomyces cerevisiae strains

Abstract: In this study, bioethanol production from steam-exploded wheat straw using different process configurations was evaluated using two Saccharomyces cerevisiae strains, F12 and Red Star. The strain F12 has been engineerically modified to allow xylose consumption as cereal straw contain considerable amounts of pentoses. Red Star is a robust hexose-fermenting strain used for industrial fuel ethanol fermentations and it was used for comparative purposes. The highest ethanol concentration, 23.7 g/L, was reached using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(91 citation statements)
references
References 45 publications
4
82
2
3
Order By: Relevance
“…The SHCF strategy elicited overall ethanol yields of 83 and 75% of the theoretical maximum, respectively, for co-fermentation of mild and severe slurry, whereas the SSCF strategy resulted in overall ethanol yields of 92 and 84%, respectively (Table 3). The improvement in ethanol yields reinforced the notion that SSF typically results in higher yields than SHF [25,26].…”
Section: Sscf Versus Shcfsupporting
confidence: 53%
See 1 more Smart Citation
“…The SHCF strategy elicited overall ethanol yields of 83 and 75% of the theoretical maximum, respectively, for co-fermentation of mild and severe slurry, whereas the SSCF strategy resulted in overall ethanol yields of 92 and 84%, respectively (Table 3). The improvement in ethanol yields reinforced the notion that SSF typically results in higher yields than SHF [25,26].…”
Section: Sscf Versus Shcfsupporting
confidence: 53%
“…The continuous release of glucose by enzymatic hydrolysis helps maintain low glucose concentrations, which kinetically favor xylose utilization in recombinant S. cerevisiae strains [21]. Typically, ethanol productivity [24] and yield are higher in SSCF than with separate hydrolysis and co-fermentation [25,26]. Ethanol yields in SSCF have been improved with modifications to the co-fermentation strategy, such as fed-batch strategies [27], enzyme feeding [28], and prefermentation [29] and combinations thereof [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…However, a comparison of SHF and SSF conducted by Rana et al (40) found that SSF was more efficient than SHF, despite using a lower reaction temperature, which is suboptimal for enzyme hydrolysis. The lower temperatures and shorter operating times required for SSF processes result in energy savings, which are a significant advantage of the system (16,41). However, some disadvantages may occur during scaling-up.…”
Section: Separate Hydrolysis and Fermentation (Shf)mentioning
confidence: 99%
“…6 Após o pré-tratamento do material lignocelulósico, as próximas etapas para a obtenção de etanol são a hidrólise enzimática e a fermentação que podem ocorrer em separado ou simultaneamente. 7 A vantagem do processo em separado (SHF) é que as temperaturas da hidrólise enzimá-tica e da fermentação podem ser otimizadas. 8 A hidrólise enzimática é realizada por celulases (endoglucanase e exoglucanase), que quebram a celulose em celobiose, e esta é, subsequentemente, convertida em duas moléculas de glicose pela β-glucosidase.…”
Section: Introductionunclassified